2014
DOI: 10.1177/1049732314523681
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D

Abstract: Vitamin D has been a topic of much research interest and controversy, and evidence is mixed concerning its preventive effects and health benefits. The purpose of our study was to explore the decision making strategies used by both primary care providers and community members surrounding vitamin D in relation to uncertainty management theory. We conducted semistructured interviews with primary care providers (n = 7) and focus groups with community members (n = 89), and transcribed and coded using the constant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…However, people usually rely on diversified sources of information [20]. When all types of media were grouped, they were cited by 63% of our participants (men especially), becoming the leading source of information, as observed in previous studies [23,28,35,36].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…However, people usually rely on diversified sources of information [20]. When all types of media were grouped, they were cited by 63% of our participants (men especially), becoming the leading source of information, as observed in previous studies [23,28,35,36].…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have shown that physicians are a major source of VitD-related information [19,23,28,31,35]. This highlights the important role played by physicians (trusted source of information) in the education of their patients [20,23,25,26]. …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“… 19 Recent research has also shown both health professionals and the general public are uncertain about many aspects of vitamin D, including how much is needed per day and how much can be easily obtained through natural sources. 50 …”
Section: Discussionmentioning
confidence: 99%